The Relationship between the Study Habits and the Academic Performance of Medical Sciences Students - Hayede Rezaie Looyeh; Seyede Fateme Seyed Fazelpour; Shadman Reza Masoule; Minoo Mitra Chehrzad; Ehsan Kazem Nejad Leili (Guilan University of Medical Sciences, 2017)
Abstract Introduction: Students study methods affect their learning and academic achievement, and the resultant process plays a role in the development cognitive and practical skills, and ultimately their future career. Determining the students' study habits and the relationship between their study habits and their academic performance can, therefore, improve their academic achievement, strengthen and modify their study habits. Objective: This study aimed to determine the relationship between the study habits and the academic performance of the students of the Guilan University of Medical Sciences. Materials and Methods: This analytical-descriptive study conducted between 2013 and2014, samples comprising 461 students from different courses at the Guilan University of Medical Sciences were selected based on a stratified random sampling method. The data collection tools included Palsane and Sharma Study Habit Inventory (PSSHI) with 8 areas (division of time, physical status, ability to read, noting, learning motivation, memory, exams, and wellness) and 45 items. The data from this research were analysed using mean descriptive and inferential statistical tests, standard deviation, Spearman s correlation coefficient, and multiple regressions with a significance level of p < 0.05. Results: The mean of the overall status of the students study habits was 48.35 ± 10.37 from 90. The academic performance of the majority (67.2%) of the students was estimated to belong to the intermediate level. Data suggests that the academic performance of the students had the highest correlation with the field of noting (p < 0.0001 and r = 0.234), while the lowest correlation was with the wellness area (p = 0.03 and r = 0.101). In general, the correlation between study habits and academic performance was significant (p < 0.0001 and r = 0.229). In addition, the study habits score can predict 6.8% of the changes in academic performance (R2 = 0.068). Conclusion: The results showed that the study habits of the students are at a relatively good or average level. In addition, owing to the existence of a significant relationship between study habits and academic performance, education administrators and planners can enhance students' study habits with the inclusion of appropriate educational content, especially their skills of noting and reading their notes, and thus improve their academic performance. There is a significant relationship between the study habits of students and their academic performance.